2012
DOI: 10.1002/ptr.4672
|View full text |Cite
|
Sign up to set email alerts
|

Damnacanthal from the Congolese Medicinal Plant Garcinia huillensis has a Potent Preferential Cytotoxicity against Human Pancreatic Cancer PANC‐1 Cells

Abstract: Screening of eight Congolese medicinal plants showed that the CHCl(3) and MeOH extracts of Aframomum melegueta (PC(50)  = 47.8 µg/mL and 13.8 µg/mL, respectively) and CHCl(3) extracts of Garcinia huillensis (PC(50)  = 17.8 µg/mL) and Securidaca longepedunculata (PC(50)  = 23.4 µg/mL) had preferential cytotoxicity against human pancreatic cancer PANC-1 cells under nutrient-deprived conditions. The active constituents of the CHCl(3) extract of G. huillensis were examined and 12 known anthraquinones were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…However, some studies have reported inconclusive associations (Romagnolo and Selmin, 2012). Flavonoids such as quercetin , rutin (Marrassini et al, 2011), hesperetin (Aranganathan and Nalini, 2012), xanthohumol (Zajc et al, 2012), 7,7''-dimethoxyagastisflavone , silymarin (Yu et al, 2012), chrysoplenetin and chrysosplenol D (from Vitex negundo) (Awale et al, 2011), formononetin, genistein (Mansoor et al, 2011), peonidin and cyaniding (two anthocyanidins) (Tanaka et al, 2012) and many others isolated from a number of medicinal plants such as Marrubium thessalum (Argyropoulou et al, 2012), Zeyheria montana (Seito et al, 2011), Spatholobus suberectus (Shim, 2011) and Glycine max (Goh et al, 2012), as well as related polyphenolic compounds such as rotenoids (Aviello et al, 2011;Kang et al, 2012), anthraquinones (Capasso et al, 1998;Dibwe et al, 2012;Lee et al, 2011aLee et al, , 2011bAviello et al, 2010) and resveratrol (Lim et al, 2012) have recently been shown to exert genoprotective, cytotoxic, antiproliferative and/or proapoptotic actions in different tumoural cell lines. More in-depth studies have shown that liquiritigenin, a flavanone found in a variety of plants including licorice, promoted apoptosis in HeLa cells, an effect associated with the up-regulation of p53 and Bax, down-regulation of Bcl-2 and surviving, release of cytochrome c and elevated activity of caspase-9 and -3 .…”
Section: Flavonoids Exert Anticancer Actions Via a Combination Of Mecmentioning
confidence: 99%
“…However, some studies have reported inconclusive associations (Romagnolo and Selmin, 2012). Flavonoids such as quercetin , rutin (Marrassini et al, 2011), hesperetin (Aranganathan and Nalini, 2012), xanthohumol (Zajc et al, 2012), 7,7''-dimethoxyagastisflavone , silymarin (Yu et al, 2012), chrysoplenetin and chrysosplenol D (from Vitex negundo) (Awale et al, 2011), formononetin, genistein (Mansoor et al, 2011), peonidin and cyaniding (two anthocyanidins) (Tanaka et al, 2012) and many others isolated from a number of medicinal plants such as Marrubium thessalum (Argyropoulou et al, 2012), Zeyheria montana (Seito et al, 2011), Spatholobus suberectus (Shim, 2011) and Glycine max (Goh et al, 2012), as well as related polyphenolic compounds such as rotenoids (Aviello et al, 2011;Kang et al, 2012), anthraquinones (Capasso et al, 1998;Dibwe et al, 2012;Lee et al, 2011aLee et al, , 2011bAviello et al, 2010) and resveratrol (Lim et al, 2012) have recently been shown to exert genoprotective, cytotoxic, antiproliferative and/or proapoptotic actions in different tumoural cell lines. More in-depth studies have shown that liquiritigenin, a flavanone found in a variety of plants including licorice, promoted apoptosis in HeLa cells, an effect associated with the up-regulation of p53 and Bax, down-regulation of Bcl-2 and surviving, release of cytochrome c and elevated activity of caspase-9 and -3 .…”
Section: Flavonoids Exert Anticancer Actions Via a Combination Of Mecmentioning
confidence: 99%
“…18 A study by Dibwe et al had earlier reported the constituents of S. longepedunculata to include four novel highly oxygenated xanthones, named muchimangins A-D. 19 Securidaca longepedunculata also displayed potent preferential cytotoxicity when used on human pancreatic cancer PANC-1 cell line in a nutrient-deprived medium. 20 However, the mechanism of anti-cancer activity of Securidaca longepedunculata root bark extract has not been elucidated nor reported. This study aims to determine the brine shrimp cytotoxicity and the anti-mitotic activity of aqueous root bark extract of Securidaca longepedunculata.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this hypothesis, we screened medicinal plants of Japan, China, and Myanmar for antiausterity activity using the human pancreatic cancer cell line PANC-1 and identified their constituents with preferential cytotoxicity [7,8]. Moreover, we examined the anti-austerity activity of eight medicinal plants used in Congolese traditional medicine and found that the CHCl 3 extracts from roots of Garcinia huillemsis (Clusiaceae), Securidaca longepedunculata (Polygalaceae), and Aflamomum melegueta (Zingiberaceae) displayed potent preferential cytotoxicity (PC 50 : 17.8, 23.4, and 47.8 μg/mL, respectively) against a human pancreatic cancer PANC-1 cell line in nutrient-deprived medium (NDM) [9]. We previously examined the constituents of the CHCl 3 extracts of G. huillensis [9] and S. longepedunculata [10].…”
mentioning
confidence: 99%
“…Moreover, we examined the anti-austerity activity of eight medicinal plants used in Congolese traditional medicine and found that the CHCl 3 extracts from roots of Garcinia huillemsis (Clusiaceae), Securidaca longepedunculata (Polygalaceae), and Aflamomum melegueta (Zingiberaceae) displayed potent preferential cytotoxicity (PC 50 : 17.8, 23.4, and 47.8 μg/mL, respectively) against a human pancreatic cancer PANC-1 cell line in nutrient-deprived medium (NDM) [9]. We previously examined the constituents of the CHCl 3 extracts of G. huillensis [9] and S. longepedunculata [10]. In a continuing study of the preferentially cytotoxic constituents of Congolese medicinal plants, we recently examined the constituents of the CHCl 3 extract of the roots of A. melegueta.…”
mentioning
confidence: 99%